2018
DOI: 10.1186/s12911-018-0693-8
|View full text |Cite
|
Sign up to set email alerts
|

Automatic seizure detection using three-dimensional CNN based on multi-channel EEG

Abstract: BackgroundAutomated seizure detection from clinical EEG data can reduce the diagnosis time and facilitate targeting treatment for epileptic patients. However, current detection approaches mainly rely on limited features manually designed by domain experts, which are inflexible for the detection of a variety of patterns in a large amount of patients’ EEG data. Moreover, conventional machine learning algorithms for seizure detection cannot accommodate multi-channel Electroencephalogram (EEG) data effectively, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 43 publications
0
52
0
Order By: Relevance
“…In this way, each time window, or segment, has 1280 data points in the 11D space. e data segmentation allows to increase the number of training samples, which is mandatory, especially in deep learning [26,29]. For the training of the network, the data from seizures were segmented with an overlap with the previous window of 0.1484 s, 0.5508 s, 1 s, for patient #5, patient #6, and patient #9, respectively.…”
Section: Eeg Segmentation and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, each time window, or segment, has 1280 data points in the 11D space. e data segmentation allows to increase the number of training samples, which is mandatory, especially in deep learning [26,29]. For the training of the network, the data from seizures were segmented with an overlap with the previous window of 0.1484 s, 0.5508 s, 1 s, for patient #5, patient #6, and patient #9, respectively.…”
Section: Eeg Segmentation and Datamentioning
confidence: 99%
“…e results, presented in terms of median true positive rate labelling by seconds is 74%, which the authors claimed to be higher than that of commercially available seizure detection software. In [29], each single-channel EEG signal is converted into a 2D plot and the plots corresponding to 22 different EEG channels are combined in 3D images depending on the mutual correlation of the intensities between the electrodes. en, using 3D kernels, a 3D CNN, with 4 convolutional layers, 3 max pooling layers, and 2 fully connected layers, has been built to detect interictal, preictal, and ictal stages in 13 epileptic patients.…”
Section: Introductionmentioning
confidence: 99%
“…For each input modality, different architectures were evaluated depending on the dimensionality of the data (1D or 2D). In another study, the authors proposed the use of 3D inputs from multi-channel EEG recordings 22 ; the results over 13 patients with 159 seizures demonstrated that 3D models surpassed 2D models in metrics such as accuracy, specificity and sensitivity in about two points. However, 3D models have a larger number of parameters to be learned, and thus require much more training samples.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been based on different deep neural network structures, such as a fully connected neural network (FCNN) 24 , convolutional neural network (CNN) 22,[25][26][27] , and recurrent neural network (RNN) 28 . These different neural networks can automatically learn discriminative features from various types of data input, including raw temporal EEG 26 , FFT results 25 , 2-dimensional (2D) representation of STFT results 29 , and 2D images of raw EEG 27 . The adoption of different input forms and network structures typically makes it difficult to directly compare performance among different deep learning methods.…”
mentioning
confidence: 99%
“…Furthermore, these studies adopted different window sizes for EEG segmentation (e.g., 1-25 , 2-29 , 3-22 , 5- 24,27 , 8-26 , and 23.6-s 28 windows). In addition, the classifiers were trained and tested on different datasets including public EEG datasets such as the Bonn 22,28 , CHB-MIT 25,29 , and Freiburg 25 datasets, or their own datasets 24,27 . Thus, it is almost impossible to directly compare the results of different studies to ascertain an optimal combination of input modalities and network structures.…”
mentioning
confidence: 99%